Developing pre-service mathematics teachers’ curriculum knowledge for designing mathematics lesson: A professional development model - Ekawati, Rooselyna; Palupi, Evangelista Lus Windyana; Kohar, Ahmad Wachidul; Putri, Hani Rizkia (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2023)
This paper aims to describe an innovative Teacher Professional Development Program (TPDP) to develop pre-service mathematics teachers’ curriculum knowledge. The participants of this study were eighteen pre-service mathematics teachers who have not learned about curriculum as a course in their teacher education program. Two different instruments to measure Pre-Service Teacher Curriculum Knowledge in the domain of statistics and algebra were delivered before and after the TPDP. The innovative TPDP for pre-service teachers in this study considered the current school mathematics curriculum as an entry object of learning. Furthermore, the triangle object such as the development of curriculum among countries, essential mathematics content, as well as designing lessons were elaborated in the model. The developed TPDP and pre-service teachers' lesson designs were described and analyzed qualitatively to see the pre-service teachers' curriculum knowledge. The result of the study shows that there is an improvement in Pre-Service Teachers' Curriculum Knowledge in almost all the components of Curriculum Knowledge, except basic skills and concepts. This implies that for designing a lesson plan, pre-service mathematics teachers need to carefully understand the school mathematics structure as a whole in a brief before the basic competence is reviewed.